Genotoxic effects in island populations of Cartagena de Indias, Colombia due to environmental exposure to mercury and cadmium [version 3; peer review: 2 approved] - Doris Gómez-Camargo; Dacia Malambo-García; Eder Cano-Pérez (F1000Research)
Background Contamination of Cartagena Bay, Colombia with heavy metals such as mercury (Hg) and cadmium (Cd) presents a major environmental and public health concern, particularly for human communities residing on nearby islands and coastal areas. These populations face enhanced exposure risks owing to their traditional fishing practices and continuous interactions with polluted marine environments. This study aimed to evaluate the genotoxic effects of environmental exposure to Hg and Cd in populations from the island zone of the Cartagena district, Bolívar. Methods Ninety-four individuals from the four island communities (study group) and 30 individuals from the urban area of Cartagena (control group) participated in this study. The blood samples were collected to measure total mercury (T-Hg) and Cd concentrations, and a Buccal Micronucleus Cytome (BMCyt) assay was used to evaluate exposure effects. Results Cadmiun levels in the blood of the study group were within the normal range and comparable to those of the control group (p > 0.05). However, the study group exhibited significantly higher T-Hg levels (7.34 μg/L) compared to the control group (2.01 μg/L), surpassing the accepted limit. Moreover, the study group showed a higher incidence of DNA damage and cell death biomarkers (p < 0.05). Additionally, significant correlations were observed between total blood Hg levels and the frequencies of micronuclei, karyorrhexis, and karyolysis. Conclusion These results suggest that island populations of Cartagena are exposed to high levels of Hg and exhibit genotoxic damage, indicating a problem that must be addressed.